Investment Portfolio Optimization on Russian Stock Market in Context of behavioral theory - N. M. Red’kin (Финансы: теория и практика, 2019)
The paper investigates possible investment portfolio optimization considering behavioral errors. The research rationale is due to the adaption of the investment recommendations for unqualified investors on the Russian stock market. In economic literature, the consequences of behavioral effects are not detailed enough when making a portfolio of Russian securities. The aim of the article is to make the most optimal portfolio based on the risk/reward ratio. The author made a hypothesis on applying various periods of profitability analysis to improve profitability indicators and increase the subjective probability of its achievement. To build a portfolio model, the behavioral portfolio theory and its optimization through linear programming were used. The study was based on modeling the investment portfolio of the most liquid stocks on the Russian stock market. Modified elements of the cumulative prospect theory with behavioral coefficients were used as indicators of profitability and probability. Based on the analysis results, the model of semi-annual portfolio analysis was proposed as a tool for portfolio optimization. The investor review of the portfolio semi-annual rate of profitability led to its best final index of effectiveness. In the medium-term assessment of portfolio profitability, the influence of behavioral factors decreases while maximizing returns with medium high risk. The research result is consistent with the basics of behavioral economics as the prospect theory regarding risk and loss aversion. Moreover, the factor of frequency of access to information and the degree of naive portfolio diversification with high profitability are promising areas for the development of research in behavioral finance. However, determining by the investor the objective probability to achieve the expected return level by using specific benchmarks is controversial.